1999
DOI: 10.1073/pnas.96.11.6096
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle-dependent regulation of RNA polymerase I transcription: The nucleolar transcription factor UBF is inactive in mitosis and early G 1

Abstract: Transcription of ribosomal RNA genes by RNA polymerase (pol) I oscillates during the cell cycle, being maximal in S and G 2 phase, repressed during mitosis, and gradually recovering during G 1 progression. We have shown that transcription initiation factor (TIF)-IB͞SL1 is inactivated during mitosis by cdc2͞cyclin B-directed phosphorylation of TAF I 110. In this study, we have monitored reactivation of transcription after exit from mitosis. We demonstrate that the pol I factor UBF is also inactivated by phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
135
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(144 citation statements)
references
References 36 publications
8
135
0
1
Order By: Relevance
“…Previous studies revealed that the shutdown of rRNA synthesis during mitosis and early G 1 phase is due to inactivation of TIF-IB/SL1 and UBF (Heix et al, 1998;Klein and Grummt, 1999). Growth-dependent regulation of Pol I, on the other hand, has been attributed to alterations in the amount or activity of TIF-IA (Buttgereit et al, 1985;Schnapp et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies revealed that the shutdown of rRNA synthesis during mitosis and early G 1 phase is due to inactivation of TIF-IB/SL1 and UBF (Heix et al, 1998;Klein and Grummt, 1999). Growth-dependent regulation of Pol I, on the other hand, has been attributed to alterations in the amount or activity of TIF-IA (Buttgereit et al, 1985;Schnapp et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Conditions that harm cellular metabolism are accompanied by profound, but reversible, changes in the rate of rRNA genes transcription. During cell cycle progression in mammals, rRNA transcription levels are finely regulated, high in the S and G2 phases they shut down in mitosis and progressively increase in G1 (Pardee, 1989;Grummt, 1999;Klein and Grummt, 1999). The regulation of cell growth and proliferation via the production of ribosomes can also be controlled at later stages, during rRNA processing or ribosome assembly.…”
Section: Introductionmentioning
confidence: 99%
“…Our data is consistent with other reports showing that there is a large increase in pre-rRNA transcript in G 2 with decreases in G 1 . 5,46 Another report done in yeast has found that the levels of rRNA transcript peaks following replication late in S phase. 4 However, this increase during S phase was only two fold, suggesting it may be due to the duplication of the genome, while we observe a 3-4 fold increase.…”
Section: Resultsmentioning
confidence: 99%
“…49 UBF is also phosphorylated and inactivated in mitosis. 5 MBD3 undergoes phosphorylation at G 2 /M by the cell cycle dependent kinase Aurora A, 50 however it is unknown whether this affects its ability to bind DNA. SL-1 is reactivated and remains bound in G 1 , 5 which is thought to allow the basal transcriptional levels of rRNA, while acetylation and phosphorylation by cdk4/cyclin D1 and cdk2/Cyclin E&A of UBF promotes its interaction with Pol I, 6,7,13 thus allowing for increased transcription.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation